Neutralization of snake venom phospholipase A(2) toxins by aqueous extract of Casearia sylvestris (Flacourtiaceae) in mouse neuromuscular preparation - Cavalcante, Walter L. G.; Campos, Tayna O.; Dal Pai-Silva, Maeli; Pereira, Paulo S.; Oliveira, Clayton Z.; Soares, Andreimar M.; Gallacci, Marcia (Elsevier B.V., 2007)
Aqueous extract of Casearia sylvestris (Flacourtiaceae) has been shown to inhibit enzymatic and biological properties of some Bothrops and Crotalus venoms and their purified phospholipase A(2) (PLA(2)) toxins. In this work we evaluated the influence of C sylvestris aqueous extract upon neuromuscular blocking and muscle damaging activities of some PLA(2)S (crotoxin from C. durissus terrificus, bothropstoxin-I from B.jararacussu, piratoxin-I from B. pirajai and myotoxin-II from B. moojeni) in mouse phrenic-diaphragm preparations. Crotoxin (0.5 mu M) and all other PLA2 toxins (1.0 mu M) induced irreversible and time-dependent blockade of twitches. Except for crotoxin, all PLA2 toxins induced significant muscle damage indices, assessed by microscopic analysis. Preincubation of bothropstoxin-I, piratoxin-I or myotoxin-II with C. sylvestris extract (1:5 (w/w), 30 min, 37 degrees C significantly prevented the neuromuscular blockade of preparations exposed to the mixtures for 90 min; the extent of protection ranged from 93% to 97%. The vegetal extract also neutralized the muscle damage (protection of 80-95%). Higher concentration of the C. sylvestris extract (1: 10, w/w) was necessary to neutralize by 90% the neuromuscular blockade induced by crotoxin. These findings expanded the spectrum of C. sylvestris antivenom activities, evidencing that it may be a good source of potentially useful PLA2 inhibitors. (c) 2007 Elsevier B.V.. All rights reserved.
Keywords: plant medicinal; Casearia sylvestris; plant antivenom; snake venoms; phospholipases A(2); neuromuscular junction